Modeling the upshots of induced temperature and water stress on germination and seedlings length of radish (Raphanus sativus L.) via hydrothermal time model - Jalal Khan; Sami Ullah; Sikandar Shah; Sadaf; Sheharyar Khan; Sulaiman (Vegetos, 2022)
Radish ( Raphanus sativus L.), a representative of the Brassicaceae family, is an extensively cultivated root vegetable across the world. Thermal time (TT), hydro time (HT), and hydrothermal time (HTT) models can be used to characterize the response of seed germination rate to temperature (T) and water potential ( ψ ). The germination behavior of radish was investigated throughout a range of constant temperatures and water potentials to evaluate the effectiveness of hydro-thermal time model and offer a data set of germination thresholds and parameters. The study was intended to simultaneously inspect the radish seed germination (SG) pattern, base water potentials ( ψ b(50) ) and cardinal temperatures across varying temperatures ( T s ) and PEG-6000 water potentials ( Ψ s ) via the hydrothermal time (HTT) model. In a laboratory experiment Raphanus sativus L. seeds were germinated at four constant T s of 15, 20, 30 and 40 °C under four different water potentials ( ψs) of 0, − 0.2, − 0.4 and − 0.6 MPa. Germination decreased significantly at ( p ≤ 0.01) from 40% at 15 °C in − 0.2 MPa to 13% in − 0.8 MPa at 40 °C. The results also revealed that radish was more sensitive to ψ than T (p ≤ 0.01). As per the significance level of the model attributes ( R 2 : 0.527), the average cardinal temperatures were 15, 20 and 40 °C for the base ( T b ), optimal ( T o ) and ceiling ( T c ) temperatures respectively. Germination energy (GE), germination rate index (GRI), germination percentage (G%), germination index (GI), mean moisture content (MMC), seed vigor index 1 and 2 (SVI-1 and SVI-2), were recorded maximum in control condition at 15 and 20 °C and minimum at − 0.8 MPa at 40 °C. The model applied here, and its attributes, may be used as a prediction tool in different SG simulation studies, each with its own set of strengths and drawbacks. The hydrothermal constant investigates the interaction influence of T and ψ on germination under diverse ecological settings using germination data, cardinal temperatures, and statistical analysis.